ISOLATION AND LIGNOCELLULOLYTIC ACTIVITIES OF FIBER-DIGESTING BACTERIA FROM DIGESTIVE TRACT OF TERMITE (Cryptothermes sp.) - Tampoebolon, B.I.M.; Bachruddin, Z.; Yusiati, L.M.; Margino, S. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The objectives of this study were to obtain the fiber-digesting bacteria isolates from termitedigestive tract and to determine the optimum conditions of growth and production of cellulase, xylanaseand ligninase enzyme of isolate. The first study was conducted to isolate and select the fiber-digestingbacteria from the digestive tract of termites based on the highest activity of cellulolytic (S), xylanolytic(X) and lignolytic (L). The second study was optimation of the growth conditions of bacteria and theenzyme production due to effect of rice straw substrate and nitrogen. The material used were dry woodtermites, rice straw, and culture medium. The design used was a completely randomized factorial design,in which the first factor was rice straw substrate (1, 2, and 3% W/V), while the second factor wasnitrogen (0.1, 0.2 and 0.3% W/V). Variables measured were cellulase, xylanase and ligninase activities.Results of the first sudy showed that the isolates obtained consisted of 3 types, those were cellulolyticbacteria (S1, S2, and S3), 3 types of bacteria xylanolytic (X1, X2, and X3) and 3 types of bacteria lignolytic(L1, L2, and L3). Meanwhile, results of the second study showed that isolates of S2, X3, and L1 had thehighest activity, those were 1.894 U/mL, 1.722 U/mL and 0.314 U/mL, respectively. In conclusion, the addition of 1% level of rice straw substrate and 0.3% of nitrogen showed the highest enzyme activity oncellulase, xylanase and ligninase.